African Small Mammals (Macroscelidea and Rodentia) Housed at the National Museum of Natural History and Science (University of Lisbon, Portugal) - Maria da Luz Mathias; Rita I. Monarca (Diversity, 2025)
The National Museum of Natural History and Science holds a historical collection of 279 small African mammal specimens (Macroscelidea and Rodentia), representing 32 species, gathered during the Portuguese colonial period in Mozambique, Angola, and Guinea-Bissau. This study examines the collection, updates the small mammal species lists for each country, and highlights its importance as a historical baseline for biodiversity research. Rodents dominate the collection, reflecting their natural abundance and diversity, while Macroscelidea are less represented. The Angolan subset of the collection has the highest number of both specimens and species represented. Mozambique is underrepresented, and the Guinea-Bissau subset offers an extensive rodent representation of the country’s inventory. The most well-represented species are Gerbilliscus leucogaster, Lemniscomys striatus, Lemniscomys griselda (from Angola), and Heliosciurus gambianus (from Guinea-Bissau). Notably, the collection includes the neo-paratype of Dasymys nudipes (from Angola). Most species are common and not currently threatened, with geographic origin corresponding to savanna and forest habitats. These findings underscore the importance of integrating historical data and current biodiversity assessments to support multidisciplinary studies on target species, regions, or countries. In this context, the collection remains a valuable key resource for advanced research on African small mammals.